Household structure, composition and child mortality in the unfolding antiretroviral therapy era in rural South Africa: comparative evidence from population surveillance, 2000–2015 - Brian Houle; Chodziwadziwa Kabudula; Dickman Gareta; Kobus Herbst; Samuel J Clark (My University, 2023)
Objectives The structure and composition of the household has important influences on child mortality. However, little is known about these factors in HIVendemic areas and how associations may change with the introduction and widespread availability of antiretroviral treatment (ART). We use comparative, longitudinal data from two demographic surveillance sites in rural South Africa (2000–2015) on mortality of children younger than 5 years (n=101 105). Design We use multilevel discrete time event history analysis to estimate children’s probability of dying by their matrilineal residential arrangements. We also test if associations have changed over time with ART availability. Setting Rural South Africa. Participants Children younger than 5 years (n=101 105). Results 3603 children died between 2000 and 2015. Mortality risks differed by co-residence patterns along with different types of kin present in the household. Children in nuclear households with both parents had the lowest risk of dying compared with all other household types. Associations with kin and child mortality were moderated by parental status. Having older siblings lowered the probability of dying only for children in a household with both parents (relative risk ratio (RRR)=0.736, 95%CI (0.633 to 0.855)). Only in the later ART period was there evidence that older adult kin lowered the probability of dying for children in single parent households (RRR=0.753, 95%CI (0.664 to 0.853)). Conclusions Our findings provide comparative evidence of how differential household profiles may place children at higher mortality risk. Formative research is needed to understand the role of other household kin in promoting child well-being, particularly in one-parent households that are increasingly prevalent.